Interactive Effects of Zinc, Copper and Manganese in Diets for Broilers - Shelton, J.L.; Southern, L.L. (International Journal of Poultry Science, 2007)
An experiment was conducted to determine the interactive effects of Zn, Cu and Mn addition to diets of 0 to 14-d old broilers on growth performance, bone breaking strength, bone ash percentage and tissue mineral concentrations. Two levels of Zn (0 or 75 ppm, as Zn sulfate), 2 levels of Mn (0 or 100 ppm, as Mn sulfate) and 2 levels of Cu (0 or 7 ppm, as Cu sulfate) were supplemented to corn-soybean meal diets in a 2×2×2 factorial arrangement. Each treatment had 6 replications with 5 chicks each and the initial and final BW were 46 and 382 g. Daily gain, daily feed intake, gain:feed, bone breaking strength and bone and pancreatic Zn concentrations were increased (p